(untitled) (Research, Society and Development, 2021)
Based on the use of Hevea brasiliensis in latex production, the species has a consolidated role in the Brazilian economy. However, at the end of the production cycle, which lasts from 25 to 30 years, resulting wood, in general, has no added value and is normally used for firewood, without further exploring its technological properties. Seeking to introduce this species into the pulp and paper industry, we aimed to determine the fiber quality of 20 commercial clones. Wood samples were collected from planted trees (11 to 12 years old) in the municipality of Selvíria - MS. We calculated wood quality indexes of H. brasiliensis for cellulose and paper, including Flexibility coefficient, Wall proportion, Runkel ratio, Slenderness ratio (Aspect ratio), and Luce’s Shape Factor. The fiber quality indexes that best indicate the potential use of wood from Hevea brasiliensis clones for cellulose and paper production were Wall Fraction, Runkel Ratio and Luce’s Shape Factor, indicating that H. brasiliensis fibers, if used for proper industrial purposes, will give origin of a rigid paper with greater bonding contact on the surface. The clones that presented better results for fiber quality indexes were IAC 311, IAC 41, IAN 873, IAC 326, IAC 40 and RRIM 725. Enabling the use of wood after the latex exploratory cycle for pulp and paper will serve as a basis for genetic improvement of these clones and expansion of forest plantations for this purpose.